A comparative study of the electrochemical corrosion behavior between Cr2N and CrN coatings. Issue 1 (31st December 2022) - Wu, Jiaojiao; Wang, Wei; Shen, Mingli; Zhu, Shenglong
ABSTRACT: Thick Cr2 N and CrN coatings were successfully prepared by arc ion plating (AIP) at a high deposition rate of more than 15 μm/h. The electrochemical corrosion behavior of Cr2 N and CrN coatings in 3.5 wt% NaCl solution was investigated comparatively using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The results showed that the corrosion current (Icorr ) of Cr2 N coating was only 0.85 nA cm −2, which was lower than that of CrN coating of 5.5 nA cm −2 . And its charge transfer resistance (Rct ) of ∼7.19 × 10 6 Ω cm 2 increased by about two orders of magnitude compared to that of CrN coating, indicating that Cr2 N coating has better corrosion resistance. Additionally, the nitride coatings showed different surface morphologies after corrosion tests, where the relatively slight corroded surface of Cr2 N coating may be related to its larger range of passive region and higher pitting potential (Epit ).